Analisis Faktor Kejadian Stunting Pada Balita : Berbasis Transcultural Nursing - weti; Nunik Andari, Fatsiwi; Kosvianti, Emi; Febriawati, Henni (Citra Delima Scientific journal of Citra Internasional Institute, 2024)
Nutritional problems in the toddler period with or without repeated illness will have an impact on the physical condition of the child's body (stunting). Malnutrition in toddlers can occur due to cultural, habitual and social factors of society. The community in the operational area of Puskesmas Betungan is known as a patriarchal community that highly values culture as one of the determinants of behavior, especially health behavior related to food. The purpose of this study was to analyze the incidence of stunting factors in toddlers based on Transcultural Nursing. This study used a quantitative design with a cross-sectional approach. The population in this study was all mothers who had toddlers, samples were taken by simple random sampling technique. The collected data were analyzed univariately and bivariately. Results: There was an association between the incidence of stunting in toddlers with technology variables (p = 0.045), family and social support factors (p = 0.048), cultural and lifestyle values (p = 0.013), and economic factors (p = 0.034). Conclusion: Although there is no correlation between the characteristics of education and the occurrence of stunting, the level of education possessed by a woman is one of the fundamental components that contribute to nutritional problems, especially stunting.